Morbidities and Mortalities among Infant of Diabetic Mother in a Newly Established Scabu of a Tertiary Care Hospital, Bangladesh - Islam, Mohammad Nazrul; Tazmin, Tanha; Siddika, Mohosina; Bhuiyan, Mohammod Kamruj Jaman (Journal of Nepal Paediatric Society, 2016)
Introduction: Diabetes mellitus has long been associated with perinatal morbidity and mortality. It complicates 2% to 3% of all pregnancies; 90% of these cases present with gestational diabetes mellitus. In our population Gestational diabetes mellitus develops among 6.7% of all pregnancies. Macrosomia (28%), hypocalcaemia (22%), hyperbillirubinaemia (19%), polycythemia (34%), perinatal asphyxia, birth injury and congenital anomaly (6-9%) are the complications of infant of diabetic mother (IDM). Materials and Methods: This prospective observational study was done in the newly established Special Care Neonatal Unit (SCANU) to determine the morbidities and mortalities among IDM babies admitted in to Mymensingh Medical College Hospital (MMCH), Bangladesh from January to March 2015. A total 50 IDM patients who admitted during this period were recruited in the study irrespective of their gestational age, birth weight, pattern and duration of maternal diabetes. Results: Male and female patients were 29 (58%) and 21 (42%). Caesarian and vaginal delivery were 43 and seven cases. Gestational and pre-gestational diabetes mothers were 35 (70%) and 15 (30%) respectively. The important morbidities in order of frequency were found perinatal asphyxia (50%), macrosomia (48%), neonatal jaundice (44%), hypoglycaemia (40%), hypocalcaemia (36%), polycythemia (28%), CHD (20%), neonatal sepsis (20%), birth trauma (12%), TTN (6%), RDS (6%), GIT problem (2%) respectively. Mortality was recorded in three patients. Conclusion: Our observations show the high prevalence of IDM (24/1000 live birth) and their various complications. Mortality and morbidity is a bit higher in IDM. Our health policy maker should give adequate emphasis on management of IDM babies. J Nepal Paediatr Soc 2015;35(3):253-256